Gender Differences in Cerebral Aneurysm Location - Ghods, Ali J.; Lopes, Demetrius; Chen, Michael (Frontiers in Neurology, 2012)
Background and Purpose: A limited number of studies consisting predominantly of ruptured aneurysms have looked at differences in anatomical distribution of aneurysms between male and females. Unlike all other causes of stroke, subarachnoid-hemorrhages (SAH) occur more often in women and are thought to be a result of both hormonal influences and variation in wall shear stress (WSS). This paper retrospectively looks at a cohort of largely unruptured intracranial aneurysms to determine if there exists a gender discrepancy in the anatomic distribution of cerebral aneurysms. Methods: A retrospective review of consecutive patients with ruptured and unruptured intradural saccular cerebral aneurysms treated endovascularly was performed. Results: 682 aneurysms were treated. 72% of the patients were women and 27% of patients presented with SAH. Among women, most aneurysms were located along the ICA (54%) while men the ACA (29%, compared to 15% in women), a discrepancy evident in both unruptured and ruptured groups. Females tended to present later in life (59 versus 55 years), with multiple aneurysms (11%, versus 6% in men), and with SAH (28%, versus 23% in men)—the majority of these ruptured aneurysms were located at the ICA (42%), while men at the ACA (47%). Additionally, the majority (68%) of ruptured ICA aneurysms were PCOM. Conclusions: Understanding the natural history of aneurysms is imperative in treating incidentally found aneurysms. Significant differences exist between the genders in relation to aneurysm location, the most pronounced at the ICA and ACA. Previously described hormonal and hemodynamic theories behind cerebral aneurysm pathogenesis seem like plausible reasons to explain these differences.